PENGARUH LATIHAN JUMP TO BOX TERHADAP POWER OTOT TUNGKAI PADA TIM SMA NEGERI 1 PANGKALAN KURAS - Hutabarat, Obet cholombus; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to determine the effect of Jump To Box Exercise on the leg muscle power ability of the Football team at SMA Negeri 1 Pangkalan Kuras. This research method uses a pretest posttest one group desaign design. The number of samples 12 with the sampling technique that is total sampling. The instrument used in obtaining data is a vertical jump with the t-test analysis technique. Based on the analysis conducted the average value of the pretest was 12.52 and the average posttest value was 13.64 with a different value of 1.11. Furthermore, t-test analysis was performed then the t-test value between the initial test and the final test Jump To Box practice on leg muscle power with a ttable at a significant level of 0.05 with degrees of freedom N-1 (11) showed that the value of tcount (2,466)> tcount ( 1,796) thus it can be concluded that there is a significant influence on the Jump To Box training on leg muscle power in the Soccer Team 1 Pangkalan Kuras High School. Key Words: Jump To Box Exercise, Leg Muscle Power